Ex-post Merger Evaluation in the UK Retail Market for Books - Tomaso Duso; Elena Argentesi; Luca Aguzzoni; Lorenzo Ciari; Massimo Tognoni (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper empirically evaluates the effects of a merger between the two largest book retail chains in the UK. We build an original dataset of book titles with data on the prices at the store level and at the national level. We then apply difference-in-differences techniques to assess the impact of the merger. A key feature of the books market is that titles become obsolete very quickly. Therefore, we compare different titles before and after the merger in an hedonic approach. Since retail mergers may have either local or national effects (or both) according to the level at which retail chains set prices, we undertake an ex post assessment of the impact of the merger at both aggregation levels. At the local level, we compare the changes in the average price charged before and after the merger in the shops located in overlap areas (i.e. areas where both chains were present before the merger) and in non-overlap areas (i.e. areas where only one chain was present before the merger). Our results do not show any significant difference between non-overlap and overlap areas where the merger could have been expected to generate the strongest effect. To investigate the effects of the merger at the national level, we employ two distinct control groups, namely the competitors and the top-selling titles. In both cases we find that the merger did not result in an increase in prices at the national level.
Keywords: K21; L44; D22; 330